HER-SAFE study design: an open-label, randomised controlled trial to investigate the safety of withdrawal of pharmacological treatment for recovered HER2-targeted therapy-related cardiac dysfunction - Robin Chung; James C Moon; Alexander R Lyon; Charlotte H Manisty; Muhummad Sohaib Nazir; Malcolm Walker; Peter Kellman; Benjamin Dowsing; Daniel Chen; Jessica Artico; Mark Westwood; Hakim-Moulay Dehbi; et al. (BMJ Open)
Introduction A quarter of breast cancers show human epidermal growth factor-2 (HER2) overexpression, where targeted therapy dramatically improves survival. However, cancer therapy-related cardiac dysfunction (CTRCD) occurs in up to 15% of patients. With the interruption of HER2 therapy, if necessary, and the initiation of heart failure therapy (HFT), HER2 CTRCD recovers in over 80% of cases. The need to continue HFT in ‘recovered’ HER2 CTRCD following completion of HER2 therapy is unclear and there are potential significant impacts on patient’s quality of life (QoL). The Randomised Controlled Trial for the Safety of Withdrawal of Pharmacological Treatment for Recovered HER2 Targeted Therapy Related Cardiac Dysfunction (HER-SAFE) aims to evaluate whether HFT can be safely withdrawn in non-high cardiovascular (CV) risk patients with ‘recovered’ HER2 CTRCD.Methods and analysis This is a multicentre, open-label randomised controlled trial investigating whether withdrawal of HFT is non-inferior to continuation in non-high CV risk, breast cancer survivors with recovered HER2 CTRCD after cancer treatment completion. The primary endpoint is the incidence of guideline-defined cardiac dysfunction or clinical heart failure. Secondary endpoints include changes in cardiac blood biomarkers, cardiovascular magnetic resonance (CMR)-derived strain and tissue mapping and heart failure symptom questionnaires. The study will recruit 90 participants who will undergo serial clinical assessment over 12 months with advanced cardiovascular imaging (CMR scans with automated analysis at baseline, 6 and 12 months), cardiac biomarker measurement (six time points over 12 months), plus complete heart failure QoL and medication disutility questionnaires. This is the first multicentre study to address this significant clinical issue.Ethics and dissemination This study was approved by the research ethics committee (London—London Bridge, 23/LO/0152). The results will be disseminated in peer-reviewed scientific journals.Trial registration number NCT05880160.